Pemanfaatan Serbuk Kayu Pohon Gayam (Inocarpus Fagiferus) sebagai Bio Adsorbent Penjerap Ion Logam Berat Pb(II) dalam Limbah Cair - Tintin Mutiara; Jefri Dimas Aziz; Muhammad Gustav Irsack (Eksergi, 2020)
Tahitian chestnut (Inocarpus fagifer) was utilized as adsorbent to eliminate heavy metal ions in wastewater. In this research, Tahitian chestnut wood sawdust was chemical modified by alkali solution from potassium hydroxide and sodium hydroxide to enhance the adsorption capacity of the sawdust. Furthermore, the effect of pH solution and soaking time to the adsorption capacity of Tahitian chestnut wood sawdust was investigated. Based on the experiment data, it can be concluded that the kinetic of adsorption Pb(II) ions onto the adsorbent Tahitian chestnut wood sawdust was well illustrated by Lagergren 2 nd order mathematic model with the value of determination coefficient (R2 ) was 0,9496.